Goma: Centers for Internally Displaced Persons - Wright, Katherine Fairfax (Consilience, 2010)
The conflict in the Democratic Republic of Congo has claimed an estimated 5 million lives—it is the deadliest conflict since World War II. Despite a 2003 peace accord, fighting continues and according to the Internal Displacement Monitoring Centre over hundreds of thousands of people are now displaced, the majority of whom are within the eastern providence of North Kivu. In response to this crisis, UNICEF and partnering agencies have set up centers for the displaced population—providing them with, among other things, shelter, food, water, and schooling.